A call to create evidence-based mental health promotion interventions for youth that are equitable across ethnic/racial subgroups: Advocates 4-ALL Youth - Kaar, Jill L.; Bowen, Anne E.; Simon, Stacey L.; Dadematthews, Adefunke; Chandrasekhar, Jessica L.; Musci, Rashelle; Pangelinan, Melissa (Frontiers in Public Health, 2023)
Background: Adolescents from historically racial and ethnic minoritized and low-income communities have higher rates of early-life and chronic difficulties with anxiety and depression compared to non-Hispanic White youth. With mental health distress exacerbated during and in the wake of the COVID-19 pandemic, there is a need for accessible, equitable evidence-based programs that promote psychological well-being, strengthen one’s ability to adapt to adversity, and build self-efficacy prior to adolescence. Methods: An evidenced-based resiliency-focused health coaching intervention was adapted using a health equity implementation framework to meet the needs of a Title I elementary school in rural Alabama (AL) that serves over 80% Black and Hispanic students. To ensure that the program met local community needs while maintaining core program educational activities, all adaptations were documented utilizing a standard coding system. Results: Leveraging an existing academic-community partnership with Auburn University and a local AL school district, a new program, Advocates 4-All Youth (ALLY), was created. Three major adaptations were required: 1) the use of local community volunteers (ALLYs) to deliver the program versus health coaches, 2) the modification of program materials to meet the challenge of varying levels of general and health-related literacy, and 3) the integration of the Empower Action Model to target protective factors in a culturally-tailored delivery to ensure key program outcomes are found equitable for all students. Conclusions: With continued increases in youth mental health distress, there is a need for the development of universal primary prevention interventions to promote mental well-being and to strengthen protective factors among youth from historically disadvantaged backgrounds. ALLY was created to meet these needs and may be an effective strategy if deemed efficacious in improving program outcomes.